2020
DOI: 10.1186/s12890-020-01274-9
|View full text |Cite
|
Sign up to set email alerts
|

Chest roentgenography is complementary to interferon-gamma release assay in latent tuberculosis infection screening of rheumatic patients

Abstract: Background: A study of latent tuberculosis infection (LTBI) burden by chest roentgenography (CXR) with reference to interferon-gamma release assay (IGRA) is still lacking in rheumatic patients of an intermediate tuberculosis burden area. Methods: We retrospectively reviewed clinical data of patients with rheumatoid arthritis (RA), ankylosing spondylitis (AS), or psoriatic arthritis (PsA) receiving LTBI screening for biologics from Jan 2013 to April 2014. Results: A total of 238 rheumatic patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The fact that 16% of our enrolled patients had a history of TB also points to Mtb as a possible ‘environmental’ factor for RA. A recent study from Taiwan has found evidence of past TB, detected by chest x-ray, in a similar proportion of IMID patients, mostly of RA [ 48 ]. In another large Taiwanese cohort, 2.38% RA patients presented a history of TB whereas TB prevalence in the control population was 1.36% [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that 16% of our enrolled patients had a history of TB also points to Mtb as a possible ‘environmental’ factor for RA. A recent study from Taiwan has found evidence of past TB, detected by chest x-ray, in a similar proportion of IMID patients, mostly of RA [ 48 ]. In another large Taiwanese cohort, 2.38% RA patients presented a history of TB whereas TB prevalence in the control population was 1.36% [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study, also from India, comparable proportions of TB cases emerged from TB contacts who were either positive or negative for TST or IGRA [ 49 ]. Sensitivity of these assays is also being debated on a wider scale [ 3 , 48 ] and the need for more sensitive assays for a reliable detection of LTBI cannot be overemphasised [ 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While guidelines have been disseminated for the screening of TB before the initiation of biological agents, such as anti-tumor necrosis factor-α (TNFα), in the context of various chronic inflammatory ailments such as rheumatoid arthritis [5,32], it is noteworthy that a consensus regarding the routine screening for TB before the administration of ICIs in cancer patients remains conspicuously absent, especially in low endemic areas. Recent retrospective investigations have unveiled that TB infection has been observed in a mere 0.1 to 1.67 % of patients following PD-1/PD-L1 therapy [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also reported that lesions on chest radiographs suggestive of previous infection with Mtb were significantly associated with positive tests for LTBI ( Uzorka et al., 2019 ). The complementary roles between chest radiograph and immunological testing methods were also reported ( Wang et al., 2020 ). Thus, people with abnormal chest radiographs should also be the focus of screening for TB infection.…”
Section: Discussionmentioning
confidence: 99%